Elections to All-Russian Constituent Assembly in Terek Region: March — December 1917 - S. V. Darchieva (Научный диалог, 2024)
This article examines the elections to the Constituent Assembly of 1917 in the Terek region. The study of this process provides valuable historical insights that can inform contemporary electoral practices, thus representing a significant scholarly issue. The objective of the research is to elucidate the specific characteristics of the electoral process within a national region. The sources include materials extracted from archival collections and regulatory documents. It is demonstrated that between February and October 1917, the Terek region experienced intense political competition, with each political faction proposing its own methods for ensuring regional stability. The local elite, having formed the “Union of United Highlanders of the North Caucasus and Dagestan,” envisioned the region as part of a democratic federal Russian republic and did not oppose the policies of the Provisional Government. Leaders of the “Union” advocated for universal suffrage and equitable representation of the region’s peoples in the Constituent Assembly. The conclusion drawn is that the elections to the Constituent Assembly had a profoundly positive impact on the development of political culture in Russia as a whole, and specifically in the Terek region.